698 Analysis of oscillations of the center of pressure in postural control (Balneo and PRM Research Journal, 2024)
Posture results from intricate interactions between the central nervous system's control mechanisms, sensory integration, and musculoskeletal responses, encompassing two levels: sustaining tonic muscle activity for posture and making adjustments to maintain balance in response to disturbances. Due to its complexity, assessing posture with simple methods is challenging, necessitating the use of advanced techniques like stabilometric platforms to measure postural stability through the center of pressure oscillations, akin to an inverted pendulum concept, offering a comprehensive understanding of postural control mechanisms. Materials and Methods: The study aims to analyze the trajectory of the center of pressure (COP) in relation to the gender of the subjects, through directional indices (DI) and oscillation ratio (OR), in the process of posture maintenance. The study included a sample of 50 young subjects (21-24 years), sports practitioners, divided into two equal groups. Results: The study findings indicate that gender does not influence COP DI. However, there's a significant disparity between anteroposterior (AP) DI values (0.70) and mediolateral (ML) DI values (0.54). The results suggest a predominant reliance on AP control mechanisms for maintaining balance, regardless of gender. When visual input is absent, there's a slight increase in AP DI (0.72) and a decrease in ML DI (0.52), indicating a shift in balance strategies. In terms of OR, significant differences are observed based on gender, oscillation direction, and visual input. Female subjects exhibit higher AP OR (6.5) compared to males (5.1). Under closed eyes conditions, both genders show decreased AP OR (6.0 for females, 4.7 for males), indicating a reliance on alternative balance strategies in the absence of visual cues. Conclusion: The study highlights the complexity of postural control and empha-sizes the influence of factors like gender and visual input on postural stability metrics, providing valuable insights for further research and clinical practice. The analysis reveals that around 60% of COP oscillations occur in the AP direction, regardless of visual input changes. This underscores the critical role of AP control in maintaining balance, suggesting targeted interventions to enhance stability should prioritize this aspect.